Excessive daytime sleepiness, morning tiredness and major adverse cardiovascular events in patients with chronic coronary syndrome. (10th May 2021) - Olszowka, M.; Held, C.; Hadziosmanovic, N.; Denchev, S.; Manolis, A.; Wallentin, L.; White, H. D.; Stewart, R. A. H.; Hagström, E.
Abstract: Background: Sleep‐related breathing disorders (SRBDs), particularly obstructive sleep apnoea, are associated with increased cardiovascular (CV) risk. However, it is not known whether individual questions used for SRBD screening are associated with major adverse CV events (MACE) and death specifically in patients with chronic coronary syndrome (CCS). Methods: Symptoms associated with SRBD were assessed by a baseline questionnaire in 15, 640 patients with CCS on optimal secondary preventive therapy in the STABILITY trial. The patients reported the frequency (never/rarely, sometimes, often and always) of: 1) loud snoring; 2) more than one awakening/night; 3) morning tiredness (MT); 4) excessive daytime sleepiness (EDS); or 5) gasping, choking or apnoea when asleep. In adjusted Cox regression models, associations between the frequency of SRBD symptoms and CV outcomes were assessed with never/rarely as reference. Results: During a median follow‐up time of 3.7 years, 1, 588 MACE events (541 CV deaths, 749 nonfatal myocardial infarctions [MI] and 298 nonfatal strokes) occurred. EDS was associated (hazard ratio [HR], 95% confidence interval [CI]) with increased risk of MACE (sometimes 1.14 [1.01–1.29], often 1.19 [1.01–1.40] and always 1.43 [1.15–1.78]), MI (always 1.61 [1.17–2.20]) and all‐cause death (often 1.26 [1.05–1.52] and always 1.71 [1.35–2.15]). MT was associated with higher risk of MACE (often 1.23 [1.04–1.45] and always 1.46 [1.18–1.81]), MI (always 1.61 [1.22–2.14]) and all‐cause death (always 1.54 [1.20–1.98]). The other SRBD‐related questions were not consistently associated with worse outcomes. Conclusions: In patients with CCS, gradually higher levels of EDS and MT were independently associated with increased risk of MACE, including mortality. Abstract :